Antibacterial Activity Test of Ethanol Extract of Torch Ginger Flowers (Etlingera elatior) Against Streptococcus Pyogenes Bacteria Causing Pharyngitis Disease in Vitro - Turnip, Nur Ulina M. Br.; Sinulingga, Siska Esperanza; Sahada, Putri (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2024)
Background: In Indonesia, practically everyone has experienced pharyngitis, an illness with a relatively high prevalence. Coughing, sore throat, and trouble swallowing are all symptoms of pharyngitis. According to the WHO, pharyngitis can be caused by a range of species, with viral and bacterial infections being the most prevalent. The goal was to investigate the antibacterial activity of kecombrang flower extract in an ethanol solvent against microorganisms that cause pharyngitis, specifically Streptococcus pyogenes. Methodology: This study was conducted utilizing laboratory experimental procedures. Bacteria were cultivated on nutrient agar media, and 70% ethanol was used to extract kecombrang blossoms. The test was conducted out using the diffusion method, which involved soaking paper discs in a solution of kecombrang flower extract at concentrations of 20%, 40%, and 60% before placing them in NA media. As a positive control, amoxicillin was utilized. The incubation procedure took 24 hours and was carried out at 370 degrees Celsius. Three inhibitory zone measurements were performed on each extract and positive control. Results: This experiment revealed that the inhibition zone generated by kecombrang flower extract as an antibacterial was an average of 9 mm at a concentration of 20%, 11.6 mm at a concentration of 40%, 12.8 mm at a concentration of 60%, and 14.8 mm at the positive control, 100 mg amoxicillin tablets. Conclusion: The results show that kecombrang flower extract has antibacterial activity against Streptococcus pyogenes bacterium and is considered strong. The best ethanol extract of kecombrang flowers is at a concentration of 60%. Statistical analysis using One Way Annova revealed significant differences between treatments (p<0.05). To confirm, a Post Hoc Tukey (HSD) test was used.